Quality of life and upper limb disability in Charcot-Marie-Tooth disease: A pilot study - Mori, Laura; Schenone, Cristina; Cotellessa, Filippo; Ponzano, Marta; Aiello, Alessia; Lagostina, Maria; Massucco, Sara; Marinelli, Lucio; Grandis, Marina; Trompetto, Carlo; Schenone, Angelo (Frontiers in Neurology, 2022)
Charcot Marie Tooth (CMT) patients present mainly lower limbs disability, with slowly progressive distal muscle weakness and atrophy, but hands impairment is a relevant problem affecting the quality of life (QoL). The evaluation of the upper limb is of primary importance. Often these patients present subclinical disorders or report difficulties in manipulating objects, with little evidence in the most used outcome measures. We aim to investigate the impact of hand impairment in the perceived QoL of CMT persons and secondly whether the Disability of Arm, Shoulder and Hand (DASH) scale can be useful in assessing upper limb abilities in CMT. We recruited 23 patients with confirmed genetic diagnosis of CMT. We performed a clinical evaluation with Sollerman Hand Function Test (SHFT), Thumb Opposition Test (TOT) and CMT examination score (CMTES). We completed the clinical assessment with DASH scale and the Short form 36 (SF36) questionnaire for a subjective evaluation of upper limb disability and quality of life. All patients also underwent an instrumental evaluation with a hand-held dynamometer measuring hand grip and tripod pinch and a sensor-engineered glove test (SEGT) to evaluate finger opposition movements in a quantitative spatial-temporal way. As expected, we found significant differences between CMT and control group performances in both clinical and instrumental assessment. Concerning QoL, we found that total score of SF36 and the SF36 Physical Composite Score (PCS) correlate with all clinical and instrumental Outcome Measures (OMs), particularly with Tripod pinch strength and TOT, which are considered major determinants of manual dexterity in CMT. DASH scale correlates with most clinical and instrumental OMs. Not surprisingly, we also found a correlation with DASH work, because CMT affects young patients engaged in work activities. However, we found a low correlation with the TOT and the dynamometer suggesting that DASH may not be the best scale for remote monitoring of upper limb disorders in CMT patients. Nevertheless, the results of our study confirm the usefulness of SF36 in recognizing the impact of upper limb disability in these subjects suggesting its use even in the remote monitoring of physical functioning.